La representación y recepción de la migración ecuatoriana en estados unidos a través de tiktok un análisis de contenido e impacto social - Vite Acosta, Carolina Jazmín (2025)
In this work, the different causes for which Ecuadorians have migrated to the United States and their impact on daily life using mobile applications, especially TikTok, will be raised and analyzed, recognizing the problem that our country has been facing for many years, among which the lack of opportunity, employment, basic services, etc. Driven by a dream of better, their lives emigrate to be able to provide their families with a more demanding future, which allows them to live in a dignified way, since they feel disappointed by the system of government and the economic and security crisis that plagues them, and of those who do not see a necessary change to be able to continue fighting within their country. Necessary and global changes are needed within the government and new opportunities that allow Ecuadorians to have benefits that allow them to cope with the crisis and help the country economically, so that our compatriots see in Ecuador a country where they can stay. Emigration destroys families on many occasions, and migration has become a social problem that is increasing with each passing year, driven by the degrading economic and social conditions gripped by scarcity of job opportunities that cause poverty in the population, which leads Ecuadorians to seek better opportunities in other countries, especially the United States.